Sub-Second Long Lifetime Triplet Exciton Reservoir for Highly Efficient and Stable Organic Light-Emitting Diode - Tang, Zhenyu (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.